Những căn cư để xác định phương hướng phát triển ngành cơ khí đến năm 2005 - Nguyễn, Đình Hỗ (2011)
Tác giả: Nguyễn Đình Hỗ; nguyễn Thị Kim Quy; Phạm Hào; Nguyễn Ngọc Anh, PTS; Nguyễn ngọc Khanh; Phan Quang Trung và nhiều người khác -- Từ khóa: Cơ khí